O Projeto “Creche & Vida”: História do atendimento a bebês e crianças pequenas na Educação Infantil pública de Sorocaba, SP. (1989 a 1992) - Aceituno, Gabriela (2023)
This dissertation recovers the historical context of care for babies and young children after the Federal Constitution of 1988, in Sorocaba, São Paulo, Brazil, and analyzes the “Creche & Vida” project. The objective is to know, recognize and communicate the dimensions of continuing education and pedagogical work with babies and very young children in this project, in addition to documenting childhood care during this period. As specific objectives, we have: to map and document the history of early childhood education in Sorocaba from the project “Creche & Vida”; relate and recognize history by valuing continuing education; get to know the conceptions of nursery, children, education and assistance for this project; to investigate ruptures and permanences in the historical process of the constitution of the teaching profession in day care centers. The research, in its methodological organization, is of a qualitative, bibliographical and documental nature, and is carried out from the reading of theses, articles, books and documents referring to the history of the day care center in the country, with attention to the process in Sorocaba, including the laws federal, state and municipal education and childhood, also analyzing news from newspapers published in the city. In addition, reinforcing the qualitative nature, the research also has episodic interviews as sources, with people who worked in daycare centers during the term of the “Creche & Vida” project, that is, between the years 1989 and 1992. the interviews carried out make it possible to identify advances achieved by the day care center over the years and also provoke reflection on various topics relevant to the quality of care for babies and young children, such as teacher learning, public policies and investments, the day care center as a educational space, considering educating and caring, as well as the infrastructure and pedagogical work, paying attention to respect for childhood and children, playing and the presence of the teacher in the day care institution.